2004
DOI: 10.1016/j.trstmh.2004.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Malaria in camps for internally-displaced persons in Uganda: evaluation of an insecticide-treated bednet distribution programme

Abstract: Summary Malaria is a key health problem among displaced populations in malariaendemic areas. Mass distribution of insecticide-treated bednets (ITN) to prevent malaria is often carried out in complex emergencies, but there are few data on the outcome or operational effectiveness of such programmes. In June 2001, Médecins Sans Frontières completed a mass distribution of ITNs (Permanet ® ) to internally displaced persons in Bundibugyo, southwest Uganda, distributing one to four nets per household, and aiming to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
61
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(69 citation statements)
references
References 13 publications
4
61
4
Order By: Relevance
“…A 2002 evaluation of bed net implementation in Uganda among displaced persons showed that after two years, 2.5% of the bed nets had burned [17]. In a double-blind controlled trial in Thailand, 1.2% bed nets (4/350) burned in 1991 [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 2002 evaluation of bed net implementation in Uganda among displaced persons showed that after two years, 2.5% of the bed nets had burned [17]. In a double-blind controlled trial in Thailand, 1.2% bed nets (4/350) burned in 1991 [18].…”
Section: Discussionmentioning
confidence: 99%
“…Only the evaluation in Uganda [17] and the trial in Thailand [18] estimated frequency: 2.5% and 1.2%, respectively. But the Thai study is old and dealt with cotton bed nets, while the Spencer study investigates Permanet ® bed nets but used in a specific context: a refugee camp.…”
Section: Discussionmentioning
confidence: 99%
“…The number of washes and location of drying are correlated with the amount of residual insecticide; nets that are washed less frequently and dried in the shade retain more insecticide than those that are washed frequently and dried in the sun [17, 18]. Other documented causes of net damage include tears on bed frames and mattresses, fire, domestic animals, rats, toenails, drying, children playing, and contact between the net and the walls of the house [12, 13]. …”
Section: Introductionmentioning
confidence: 99%
“…In a previous study, it was shown that user-determined end of net life was defined largely by the condition of the net and the presence of mosquitoes in the net due to holes [20]. Observational studies show that more holes in the net make the net less effective at preventing mosquito entry [12, 21]. …”
Section: Introductionmentioning
confidence: 99%
“…Over ninety United Nations High Commissioner for Refugees (UNHCR) refugee camps in Africa and Asia are affected by malaria [8][9], Cholera and Malaria in refugee camps along the border between Syria and Turkey [10] and measles in refugee camps in Kenya, Ethiopia, Tanzania and other UNHCR refugee camps across Africa and Asia [9;11;12]. Other diseases that have been reported include Hepatitis E among refugees and IDPs in Upper Nile, South Sudan [10;13], bloody diarrhoea, watery diarrhoea and fever of unknown origin in Kosovar refugee camps in the former Yugoslav Republic of Macedonia and again over ninety refugee camps across Africa and Asia [9;14].…”
Section: Introductionmentioning
confidence: 99%